The Relationship between Halal Status Knowledge and the Korean Food Products Purchasing Practices in DIY’s Muslim Society - Rachmawati Widyaningrum (Jurnal Ilmiah Ekonomi Islam, 2023)
Background: Halal food products have great market potential in Indonesia, considering that majority of its population is Muslim. However, it is followed by the challenges of the increase in imported food products interest, particularly Korean products. Some Korean imported foods do not have a Halal certificate, although the producers or distributors already sell the products widely. Furthermore, the Muslim society's knowledge about halal food products is essential to prevent non-halal products purchasing. Objectives: This study aims to determine the relationship between the Muslim community in Daerah Istimewa Yogyakarta (DIY) halal status knowledge and their practice of purchasing food products from Korea. Methods: This study is a quantitative cross-sectional online study conducted from February to May 2022. The total number of participants was 112 with the inclusion criteria: Moslem, aged a minimal 14 years old, live in Daerah Istimewa Yogyakarta (DIY), and a Korean food consumer. Results: There was a significant relationship between the knowledge of the Muslim community on the practice of Korean food product purchasing.